Perancangan Model Stacker Crane Flexible Manufacturing System untuk Pembelajaran di Institusi Pendidikan - Ari Setiawan (Universitas Katolik Parahyangan, 2021)
Flexible Manufacturing System (FMS) is one of the modern production systems that support the implementation of Industry 4.0. An educational institution plans to build an FMS model for learning the modern production systems. The FMS is a manufacturing system consisting of a set of automatic workstations connected to a material handling system where all activities are controlled by a computer system. The material handling system consists of a material storage system and a transportation system, one example of a transportation system is the stacker crane. In this research, the stacker crane model has been built which consists of three main components, which are the bottom frame, the mast, and the carriage. This component is equipped with stepper motors, leadscrews that are controlled by the micro controller and an application on Android. The stacker crane model is tested to retrieve and deliver the stereofoam material model to the destination which is controlled by the user using an application on Android. The characteristics of the stacker crane model can move the workpiece with a maximum error of 2 mm in the positive x-axis direction, 2 mm in the negative x-axis movement, up to 2 mm positive y-axis, downward at negative y-axis direction 2 mm.